Robust operational level schedule recovery in liner shipping services - Xie, Chentao (2016)
The prevalence of delays and high degree of uncertainty in liner shipping have created the problem of operational level schedule recovery. This study proposes an operational level robust solution for schedule recovery for one ship by speed increases, addressing the uncertainties in port waiting time and handling time, as well as the variation in the actual speed. A mixed-integer linear programming (MILP) model is established. Through discretization of stochastic variables, robust solutions can be produced that minimize the total costs of schedule recovery, which include bunker cost, cost of late-delivery, and cost of misconnection, under the near worst-case scenario. The model can be solved using off-the-shelf MILP solvers and the model is designed to be solved after every occurrence of disruption. The solution of the model assists operational level management decisions and is easy to understand and implement. By considering the variations in the actual speed, which was ignored by past studies, the model enables more accurate and practical real-time emergency response.